Two-phase exponential model of wealth distribution - Ognjen Radović; Zoran Tomić; Jelena Z. Stanković (Economic Themes, 2020)
The topic of wealth and money distribution attracts great attention of economists, as well as researchers from other scientific fields, such as statistical physics and econophysics. An increasing number of models and simulations are being created in order to understand the process of wealth distribution and reaching the steady state of the distribution system. Also, the number of papers dealing with analysis and determining the distribution proportion is constantly growing, and, unlike the previous years, when the Pareto principle was '80-20', today that principle could be '90-10'and even '90-20'. In this paper we present an agent-based simulation model derived from econophysics that describes the dynamics of wealth distribution. Two models of exponential function are tested: a one-phase model that uses the Newton's law of cooling and a two-phase exponential function model. We found that exponential decreasing function adequately described the dynamics of wealth distribution, especially in the models without the possibility of borrowing money, and the validity of the Pareto principle “80-20” in these models could be confirmed.
Keywords: D31; G51; C63; E47; 330; wealth distribution; exponential functions; Newton's law ofcooling